Diagnostic and therapeutic value of micro-rnas in inflammatory bowel disease - Berezin, A. E.; Poplyonkin, E. I.; Березін, Олександр Євгенійович; Попльонкін, Є. І. (My University, 2020)
Inflammatory bowel disease (IBD) is a heterogeneous chronic idiopathic inflammatory disease thatincludes ulcerative colitis (UC) and Crohn's disease with uncertain etiology and pathogenesis. Theprevalence of IBD has steadily increased worldwide, affecting numerous groups of people in bothdeveloped and developing countries. Current guidelines are being re-defined with the aim for pa-tients with established IBD to achieve mucosal healing and complete morphological figures withminimal drug toxicity, to diminish the likelihood of extra-intestinal manifestations and dysplasia/colorectal cancer, and to prevent the need for surgery. Many patients with established IBD mayrequire conventional treatment, as well as alternative treatment, due to non-response, loss of re-sponse, or intolerance to treatment regimen. In this context, stratification of risk and managementof IBD could be based on personified strategy predominantly allocated to core components ofpathogenesis of the disease. MicroRNAs (miRNAs) are defined as non-coding short RNAs which areinvolved in various stages of the natural evolution of IBD. Recent animal and clinical studies haveshown the role of single nucleotide polymorphisms (SNPs) and signature of miRNAs in susceptibil-ity to IBD, risk of clinical and histological exacerbation, and remission. The aim of the review is tosummarize the knowledge regarding use of miRNAs as biomarkers and molecular targets in IBD.
Keywords: inflammatory bowel disease; ulcerative colitis; Crohn's disease; miRNAs; biomarkers; prediction; prognosis